Inspection and Maintenance of State Buildings to Enhance Building Performance: A Case Study of the Digital Economy Promotion Agency - Wongsakda, Prajak; Snongtaweeporn, Teeradej; Kongsong, Waranon; Pooworakulchai, Chaiwat (Journal of Dhamma for Life, 2025)
This research aims to study how to improve the efficiency of state building inspection and maintenance, using the Digital Economy Promotion Agency (DEPA) as a case study. The objectives are to 1) study and analyze the factors affecting DEPA's building inspection and maintenance; 2) identify and analyze the obstacles and supporting factors in implementing building inspection and maintenance; and 3) analyze approaches to applying digital technology to increase the efficiency of building inspection and maintenance in government agencies. The research uses a mixed-methods approach, employing both quantitative and qualitative research methods. The sample consists of 158 DEPA personnel for the questionnaire, and 15 executives and experts for in-depth interviews. The research instruments are questionnaires and interview guides. The research found that factors affecting the efficiency of state building inspection and maintenance include organization policy, technology, budget, and management. Organization policy was found to be the most influential factor. Problems and obstacles identified include budget limitations, a shortage of specialized personnel, and outdated laws. In addition, the research proposes guidelines for applying digital technology to increase the efficiency of building inspection and maintenance in government agencies. The results of this research can be used to improve the building inspection and maintenance processes of the Digital Economy Promotion Agency to be more efficient, and can serve as a guideline for the development of policies and plans for the management of buildings of government organizations.